Population Registry Cards for Inhabitants of Lodz as a Source of Information About the City’s Population in the 19th and Early 20th Century - Repczyńska-Górczak, Helena; Antosik, Szymon; Chmielarz, Małgorzata (Studia Historiae Oeconomicae, 2022)
During the industrialization period of the city of Lodz, one of the most important industrial centres in the Kingdom of Poland (the former Russian Partition), experienced a dynamic population growth caused by migratory movement from rural areas to the city. The population registry cards for inhabitants of Lodz contained information on dates of birth (sometimes on dates of death), place of birth, religious denomination, nationality, and address of residence in the city, as well as the number of children born in a family. The aim of this paper is to present population registry cards of permanent and non-permanent residents of the city of Lodz deposited in the State Archives in Lodz, as a source for research on urban society during the period of industrialization. In this work, the use, quality, and reliability of population registry cards, as well as their research limitations for studies are discussed.